Amphiphilic Janus Particles Generated via a Combination of Diffusion-Induced Phase Separation and Magnetically Driven Dewetting and Their Synergistic Self-Assembly - Wang, Xiuyu (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.